Beginning partial differential equations - O'Neil, Peter V. (Pure and applied mathematics, 2014)
"This Third Edition provides a solid introduction to partial differential equations, particularly methods of solution based on characteristics, separation of variables, as well as Fourier series, integrals, and transforms"--